Expression of hypothalamic kisspeptin, neurokinin B, and dynorphin A neurons attenuates in female Zucker fatty rats. (5th February 2018) - Nakao, Kimihiko; Iwata, Kinuyo; Takeshita, Toshiyuki; Ozawa, Hitoshi
Highlights: KNDy neurons in the ARC were attenuated in Zucker fatty rats compared with Zucker lean rats. The number of Kiss1 neurons in the AVPV and GnRH neurons in the mPOA did not differ between Zucker lean and fatty rats. KNDy neurons could be involved in infertility due to obesity with leptin signaling dysfunction. Abstract: Zucker fatty (ZF) rats are considered to be an obese model due to leptin receptor abnormality and such rats show infertility. Pulsatile gonadotropin-releasing hormone/luteinizing hormone (LH) secretion, which is important for follicular development in females, is considered to be controlled by KNDy neurons coexpressing kisspeptin, neurokinin B (NKB), and dynorphin A (DynA), encoded by Kiss1, Tac3, and Pdyn, respectively, in the hypothalamic arcuate nucleus (ARC). The purpose of this study is to examine the expression of KNDy neurons in female ZF rats by histochemical approach because pulsatile LH secretion is suppressed. Zucker lean (ZL) rats served as a control group. Animals were ovariectomized and subcutaneously implanted with a silicon tube containing estradiol to produce plasma level of estradiol during diestrus. Plasma LH levels decreased in ZF rats compared with ZL rats. The expressions of each mRNA ( Kiss1, Tac3, and Pdyn ) and each peptide (kisspeptin, NKB, and DynA) in the ARC significantly decreased in ZF rats compared with ZL rats. However, the number of Kiss1 neurons in the anterior ventral periventricular nucleus did not significantly differ between the two groups. These results suggest that dysfunction of leptin signaling negatively affects KNDy neurons in the ARC, resulting in reproductive dysfunction caused by suppression of the LH pulse.